1988
DOI: 10.1002/art.1780310513
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of infection among patients with rheumatoid arthritis versus patients with osteoarthritis or soft tissue rheumatism

Abstract: We compared the frequencies and types of infections that occurred in 448 patients with rheumatoid arthritis (RA) versus those occurring in 185 control patients who had osteoarthritis or soft tissue rheumatism. At least 1 infection developed in 23% of the RA patients and in 27% of the control patients. Using a series of risk factors, we found no substantial difference in the risk of infection in RA patients compared with that in control patients. Some of these factors, such as being female, having poor function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0
3

Year Published

1989
1989
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 13 publications
4
20
0
3
Order By: Relevance
“…None of the patients had Felty's syndrome, 65 and neither neutropenia nor lymphopenia was 23 found during the study. 1 In the MTX group functional class and 43 mobility scores were significantly higher (that 49 is, worse) than in the control group (table 1). 17…”
Section: Statisticsmentioning
confidence: 88%
“…None of the patients had Felty's syndrome, 65 and neither neutropenia nor lymphopenia was 23 found during the study. 1 In the MTX group functional class and 43 mobility scores were significantly higher (that 49 is, worse) than in the control group (table 1). 17…”
Section: Statisticsmentioning
confidence: 88%
“…However, a recent study found no difference in the frequency or type of infection in RA patients compared with patients with osteoarthritis (04) or soft tissue rheumatism (14). RA patients who had been receiving corticosteroids did have a higher incidence of infection.…”
mentioning
confidence: 98%
“…Furthermore, the severity of the disease itself has been shown to correlate with the infection rate [70]. Several other factors such as skin lesions, invasive investigations and immobility due to the damage of the articular surface, may favour articular and cutaneous infections [71]. Finally, glucocorticoid therapy may contribute to the development of infections, while controversial results are reported about the influence of disease-modifying antirheumatic drugs (DMARDs) [71].…”
Section: Rheumatoid Arthritis and Infectionsmentioning
confidence: 98%
“…Several other factors such as skin lesions, invasive investigations and immobility due to the damage of the articular surface, may favour articular and cutaneous infections [71]. Finally, glucocorticoid therapy may contribute to the development of infections, while controversial results are reported about the influence of disease-modifying antirheumatic drugs (DMARDs) [71]. With regard to VPDs, it is well known that RA patients have an increased mortality due to infectious respiratory diseases.…”
Section: Rheumatoid Arthritis and Infectionsmentioning
confidence: 99%